2012
DOI: 10.19030/jabr.v29i1.7573
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Investors, Earnings Management And Mispricing Of Accruals: Evidence From China

Abstract: This study examines the role of institutional investors in the pricing of normal accruals and discretionary accruals using the firms listed in the Chinese A-share Market. The results show that significant overpricing of discretionary accruals exists for individual investors and institutional investors, suggesting that they are both misled by the earnings management, while institutional investors are associated with significantly less overpricing. With respect to normal accruals, we find there is no evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Institutional investors with their power of vote play an important role in the selection and independence of the corporate boards . Moreover, their active involvement in the board meetings restricts the directors to misstate or hide corporate information (Zeng et al, 2013). Lin et al (2009) reported that financial institutions empower the internal audit committee of the corporate board and compel the management to formulate aggressive corporate disclosure policies (Lin et al, 2018).…”
Section: Litigation Risk Institutional Ownership and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Institutional investors with their power of vote play an important role in the selection and independence of the corporate boards . Moreover, their active involvement in the board meetings restricts the directors to misstate or hide corporate information (Zeng et al, 2013). Lin et al (2009) reported that financial institutions empower the internal audit committee of the corporate board and compel the management to formulate aggressive corporate disclosure policies (Lin et al, 2018).…”
Section: Litigation Risk Institutional Ownership and Firm Performancementioning
confidence: 99%
“…Institutional investors with their power of vote play an important role in the selection and independence of the corporate boards (Waheed and Malik, 2021). Moreover, their active involvement in the board meetings restricts the directors to misstate or hide corporate information (Zeng et al. , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%